An evaluation of the NR-1000F Auto Refractometer in high refractive errors. Issue 9 (September 1987) - Nayak, B. K.; Ghose, S.; Singh, J. P.
Abstract : The manifest refractions of 37 high myopic and 16 high hypermetropic eyes in a total of 28 patients, aged 5 to 42 years, were determined on the Nikon NR-1000F Auto Refractometer. The data obtained were compared with the final clinical prescriptions for these eyes and analysed for degree of agreement for the spherical equivalents, sphere components, and cylinder powers and axes. The Auto Refractometer recordings for all the different refractive components were observed to skew towards more minus in the high myopic eyes but more plus in the high hypermetropes. The possible significance of these skewing patterns is discussed with reference to our earlier studies.